The Occurrence of Metabolic Syndrome in The Elderly Population (Eurasian Medical Research Periodical, 2023)
Metabolic syndrome (MS) is visceral obesity, decreased sensitivity of peripheral tissues to insulin, hyperinsulinemia, dyslipidemia, all types of changes in metabolism, symptoms that lead to the development of type 2 diabetes mellitus and arterial hypertension, and the deterioration of the health of the population is a complex. Currently, the problem of metabolic syndrome is one of the main medical, social and economic trends of modern society, which leads to a decrease in life expectancy and deterioration of its quality. The presented article examines modern views on the problem.